Remove Service Charge on IBFTs to Encourage Digital Transactions (The Pakistan Development Review, 2025)
The State Bank of Pakistan (SBP) announced on June 16, 2021, that it has now allowed banks to charge a transaction fee of 0.1 percent of the transaction or PKR 200, whichever is lower on Inter-Bank Funds Transfers (IBFTs). SBP has made compulsory free-of-cost IBFTs of up to PKR 25,000 per month per account. For accounts exceeding the limit, the banks will charge the transaction fee as mentioned above. Following the onset of the COVID-19 pandemic, on March 19, 2020, the Government of Pakistan and SBP decided to make all IBFTs free of charge. The idea behind this decision was to limit consumer visits to banks and thus restrict the COVID-19 threat. Before that, the banks were allowed to charge a transaction fee on IBFTs as per SBP’s defined schedule of charges. The practice did continue for a little over a year until after the third wave, the state bank, as mentioned above, assumed an improved COVID-19 position for reviewing the policy and thus reimposed the charges on digital funds transfer. Since then, Pakistan has entered the fourth pandemic wave as a much deadly delta variant and other new variants grow rapidly in Pakistan. Consequently, the basis of this review and policy change can be contested on the pandemic spread grounds, but for now, this policy viewpoint discusses the decision from an economic and financial perspective.